2022
DOI: 10.3390/jcm11030623
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction after Hematopoietic Stem Cell Transplantation: A Review Based on Physiopathology

Abstract: Endothelial dysfunction (ED) is frequently encountered in transplant medicine. ED is an argument of high complexity, and its understanding requires a wide spectrum of knowledge based on many fields of basic sciences such as molecular biology, immunology, and pathology. After hematopoietic stem cell transplantation (HSCT), ED participates in the pathogenesis of various complications such as sinusoidal obstruction syndrome/veno-occlusive disease (SOS/VOD), graft-versus-host disease (GVHD), transplant-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 228 publications
(263 reference statements)
0
13
0
Order By: Relevance
“…During allo-HCT, ECs can be directly damaged and/or activated via multiple mechanismsi) chemotherapy and radiation included in the conditioning regimen; ii) cytokines released by injured tissues; iii) translocation of endotoxins through the damaged gastrointestinal tract as well as iv) immunosuppressive prophylactic regimens used to prevent acute GVHD, Figure 1. Apart from these early factors, ECs are also a target of alloreactive donor T cells that recognize the HLA mismatched antigens on ECs and mediate EC damage (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During allo-HCT, ECs can be directly damaged and/or activated via multiple mechanismsi) chemotherapy and radiation included in the conditioning regimen; ii) cytokines released by injured tissues; iii) translocation of endotoxins through the damaged gastrointestinal tract as well as iv) immunosuppressive prophylactic regimens used to prevent acute GVHD, Figure 1. Apart from these early factors, ECs are also a target of alloreactive donor T cells that recognize the HLA mismatched antigens on ECs and mediate EC damage (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Acute graft-versus-host disease (GVHD) mediated by alloreactive T cells in the donor graft is a frequently fatal complication and the leading cause of non-relapse mortality (NRM) in patients post allo-HCT. Transplant-associated microangiopathy (TA-TMA), veno-occlusive disease (VOD), idiopathic pneumonia syndrome and accelerated arteriosclerosis are vascular injury syndromes that occur after allo-HCT ( 5 ). During allo-HCT, ECs can be directly damaged and/or activated via multiple mechanisms – i) chemotherapy and radiation included in the conditioning regimen; ii) cytokines released by injured tissues; iii) translocation of endotoxins through the damaged gastrointestinal tract as well as iv) immunosuppressive prophylactic regimens used to prevent acute GVHD, Figure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an association between maximal weight gain and aGVHD and between weight gain and bone marrow reconstitution was observed. Clinical studies have suggested that endothelial dysfunction and damage are involved in the development and severity of aGVHD [18]. Since aGVHD is an inflammatory process, it is likely that both endothelial cells and capillary leakage are important in the pathogenesis [13,18], and hence that weight gain is associated with the development of aGVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have suggested that endothelial dysfunction and damage are involved in the development and severity of aGVHD [18]. Since aGVHD is an inflammatory process, it is likely that both endothelial cells and capillary leakage are important in the pathogenesis [13,18], and hence that weight gain is associated with the development of aGVHD. Finally, we found a significant correlation between weight increase and mortality risk among allo-HSCT recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular histones are pro-thrombotic, toxic, and pro-inflammatory, and they increase endothelial permeability [ 5 , 6 ]. Histones disturb cell membrane architecture, membrane permeability, calcium influx and oxidative stress through interactions with cell membrane phospholipids as well as through toll-like receptor (TLR) 2 (TLR-2) and TLR-4 [ 7 ] expressed on endothelial cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%